Book Notes [60, Fall 2007] - Finkel, Alvin (Labour / Le Travail, 2007)
The article briefly reviews "Undelivered Letters to Hudson’s Bay Company Men on the Northwest Coast of America, 1830-1857," by Judith Hudson Beattie and Helen M. Buss, "Wartime Images, Peacetime Wounds: The Media and the Gustafsen Lake Standoff," by Sandra Lambertus, “'We, Too, Are Americans': African American Women in Detroit and Richmond, 1940-1954," by Megan Taylor Shockley, "Promise Unfulfilled: Unions, Immigration, and the Farm Workers," by Philip L. Martin, "From Charity to Social Work: Mary E. Richmond and the Creation of an American Profession," by Elizabeth N. Agnew, "Forging America: Adventurers, Ironworkers, and America’s Industrial Revolution," by John Bezis-Selfa, "Working Women in Mexico City: Public Discourses and Material Conditions, 1879-1931," by Susie E. Porter, "The Social Bases of Nazism 1919-1933," by Detlef Mühlberger, "Women and the Labour Market in Japan’s Industrialising Economy: The Textile Industry Before the Pacific War," by Janet Hunter, "Drugs, Labor, and Colonial Expansion," edited by William Jankowiak and Daniel Bradburd, "The Making of a Cybertariat: Virtual Work in a Real World," by Ursula Huws, "Drugs, Labor, and Colonial Expansion," edited by William Jankowiak and Daniel Bradburd, "Parecon: Life After Capitalism," by Michael Albert, "Thinking Past Terror: Islamism and Critical Theory on the Left," by Susan Buck-Morss, "Memoirs of a Media Maverick," by Boyce Richardson, "Canada and the Cold War," by Reg Whitaker and Steve Hewitt, and "Sticking to the Union: An Oral History of the Life and Times of Julia Ruuttila," by Sandy Polishuk.
Keywords: BOOKS -- Reviews; CANADA & the Cold War (Book); HEWITT, Steve; MEMOIRS of a Media Maverick (Book); Nonfiction; POLISHUK, Sandy; RICHARDSON, Boyce; STICKING to the Union: An Oral History of the Life & Times of Julia Ruuttila (Book); WHITAKER, Reg